2000
DOI: 10.1177/000348940010901005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intralaryngeal Carbon Dioxide and Acetazolamide on the Laryngeal Chemoreflex

Abstract: Sudden infant death syndrome is the leading cause of death in infants in the United States. The laryngeal chemoreflex (LCR) is thought to contribute to its pathogenesis. In adult animals, increasing levels of intralaryngeal CO2 result in a decrease in ventilatory activity. Intravenous acetazolamide (AZ) abolishes this response. The purpose of this study was to determine the effects of intralaryngeal CO2 and AZ on the LCR and respiratory physiology of piglets under normoxic and hypoxic conditions. We applied 0%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
2
9
1
Order By: Relevance
“…In most infant animals, this response is relatively short‐lived, and resumption of respirations is followed by a return to cardiovascular stability 15–17, 22. In some animals, however, the respiratory drive remains depressed and prolonged and often fatal apneas ensue 23–27. It is also possible to elicit the laryngeal chemoreflex using organic stimuli, such as carbohydrates and milk 14, 28–31.…”
Section: Specific Aims and Objectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…In most infant animals, this response is relatively short‐lived, and resumption of respirations is followed by a return to cardiovascular stability 15–17, 22. In some animals, however, the respiratory drive remains depressed and prolonged and often fatal apneas ensue 23–27. It is also possible to elicit the laryngeal chemoreflex using organic stimuli, such as carbohydrates and milk 14, 28–31.…”
Section: Specific Aims and Objectivesmentioning
confidence: 99%
“…The laryngeal chemoreflex‐induced apnea usually lasts less than 10 seconds 15–17, 22. In some animals, the response can last longer, resulting in severe hypoxia and potentially death 23–27. Severe or fatal laryngeal chemoreflex responses are seen only in the very young, and have been shown to be present in a variety of species 19, 29, 32–35.…”
Section: Specific Aims and Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, it has been observed that two young animals that undergo laryngeal chemostimulation under seemingly similar physiologic conditions can have marked differences in response severity. 10,[14][15][16][17] Some animals may recover uneventfully, and others may have profound or fatal responses. When laryngeal stimulation is performed under hypoxic conditions, one of two responses has been observed: a shorter, more transient response or a more profound, fatal response.l'' It has been shown that when laryngeal stimulation is performed under normoxic conditions, resumption of respiration occurs when the PaC02 reaches a certain threshold.l'' In that study, severity of response, as defined by apnea duration, was associated with the Pa02 at the time respiration was resumed.…”
Section: Introductionmentioning
confidence: 99%
“…However, the results are not UnIformly profound; the reasons for this are not fully understood. [14][15][16][17][18] One explanation for the lack of uniformly fatal responses to hypoxic stimulation may be that during prestimulation hypoxia, the ventilatory drive is stimulated and remains stimulated during the LCR, resulting in shorter and milder responses.P However, this does not explain why some animals respond to hypoxic stimulation with profound and fatal apneas and why others have more transient and milder responses. It is also plausible that it is the rate of change in Pa02 during the LCR, rather than the value of the end-apnea Pa02, that determines the response severity, as both of these factors appear to~e associated with response severity in the normoxic model.…”
Section: Introductionmentioning
confidence: 99%